Repetitive noxious neonatal stimuli increases dentate gyrus cell proliferation and hippocampal brain‐derived neurotrophic factor levels. Issue 4 (23rd December 2013) - Malheiros, J.M.; Lima, M.; Avanzi, R.D.T.; Gomes da Silva, S.; Suchecki, D.; Guinsburg, R; Covolan, L.
ABSTRACT Neonatal noxious stimulation has been proposed to model pain triggered by diagnostic/therapeutic invasive procedures in premature infants. Previous studies have shown that hippocampal neurogenesis rate and the behavioral repertoire of adult rats may be altered by neonatal noxious stimuli. The purpose of this study was to evaluate whether noxious stimulation during neonatal period alters the nociceptive response and dentate gyrus neurogenesis when compared to rats subjected to a single noxious stimulus in late infancy. Plasma corticosterone and hippocampal brain‐derived neurotrophic factor (BDNF) levels were measured. Neurogenesis in the dentate gyrus was evaluated in adolescent rats (postnatal day 40; P40) exposed twice to intra‐plantar injections of Complete Freund's adjuvant (CFA) on P1 and P21 (group P1P21) or P8 and P21 (P8P21) or exposed once on P21 (pubertal). On P21, one subset of animals received 5‐bromo‐2′‐deoxyuridine (BrdU) and was euthanized on P40 for identification of proliferating cells in the dentate gyrus. Another subset was sampled for thermal response or plasma corticosterone measurement and hippocampal BDNF levels. Proliferative cell rate in dentate gyrus was the highest in all re‐exposed groups (P < 0.001), except for P8 females (P8P21F), revealing also a sex difference, where P8P21 males showed higher rate than females (P < 0.001). Stimulated groups took longer than CTL animals to lick the paws (P < 0.001), regardless of the age when the noxious stimulus was applied. Re‐exposed groups had lower corticosterone plasma level (P1P21 M and F, P8P21M) than controls. On the contrary, hippocampal BDNF was increased in males from both re‐exposed groups. These results show that infant noxious stimulation in neonatally previously stimulated rats is related to high proliferation in the DG and this association seems to be modified by the animal's sex. The new generated dentate granule cells in the hippocampus may have a role in the long‐term behavioral responses to neonatal nociceptive stimulation. Noxious stimulation in the neonatal period results in sex‐dependent neurogenic response. © 2013 Wiley Periodicals, Inc.